Persepsi Mahasiswa Semester 5 Terhadap Pola Tidur dan Dampaknya pada Tingkat Stres - Muhammad Sidik; Kaisyah Kamila; Shabrina Nur Ramadhani; Aliya Mumtaz Zahra; Arif Saefudin (At-Tadris: Journal of Islamic Education, 2026)
Unregulated sleep patterns are often experienced by students, mainly due to dense academic and non-academic activities. This study aims to find out how 5th semester students perceive their sleep patterns and their impact on stress levels. The method used is descriptive quantitative with a cross-sectional approach. A total of 100 5th semester students were selected purposively and filled out questionnaires as research instruments. The study showed that most respondents (72%) had irregular sleep patterns with an average sleep duration of less than six hours per night. In addition, 68% of students admitted that they experienced stress at a moderate to high level. Students claim that lack of sleep makes them tired, difficult to focus, and emotional. From these results, it can be concluded that poor sleep patterns are related to increasing stress levels. Therefore, it is important for students to start paying attention to the quality of sleep in order to maintain mental health and academic performance.